2016
DOI: 10.1037/rel0000027
|View full text |Cite
|
Sign up to set email alerts
|

Dogmatism and mental health: A comparison of the religious and secular.

Abstract: Religiousness has frequently been found to be associated with higher reported mental health levels than those found in individuals lower in reported religiousness. These results have often been inferred by scholars to mean that secular groups have poorer levels of mental health despite the fact that secular populations have rarely been included in studies. In this study, an ideologically diverse sample of 4,667 respondents was included to determine the relationships among general dogmatism levels, existential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 72 publications
(93 reference statements)
3
31
1
Order By: Relevance
“…Generally, though, (non)religiousness and (non)spirituality were not independently predictive of posttraumatic growth. Further, the current study, like previous examinations of trauma (Koenig, 2012;Moore & Leach, 2016), natural disasters (Aslam & Kamal, 2015;Aten et al, 2019), and religiousness, suggested higher levels of institutional religiousness may provide some protection against negative trauma-related outcomes and religiousness and spirituality may facilitate posttraumatic growth at higher levels of trauma intensity. However, the relationship between positive outcomes and religiousness may be driven by active participation in a personal belief system, rather than strength of identification alone (Berthold & Ruch, 2014) or social engagement (McCaffree, 2019).…”
Section: Integration With Previous Researchsupporting
confidence: 72%
See 1 more Smart Citation
“…Generally, though, (non)religiousness and (non)spirituality were not independently predictive of posttraumatic growth. Further, the current study, like previous examinations of trauma (Koenig, 2012;Moore & Leach, 2016), natural disasters (Aslam & Kamal, 2015;Aten et al, 2019), and religiousness, suggested higher levels of institutional religiousness may provide some protection against negative trauma-related outcomes and religiousness and spirituality may facilitate posttraumatic growth at higher levels of trauma intensity. However, the relationship between positive outcomes and religiousness may be driven by active participation in a personal belief system, rather than strength of identification alone (Berthold & Ruch, 2014) or social engagement (McCaffree, 2019).…”
Section: Integration With Previous Researchsupporting
confidence: 72%
“…Although religiosity may buffer the adverse impact of stress (Lawler-Row & Elliott, 2009;Koenig, 2012;Moore & Leach, 2016) and religiosity and well-being are positively associated (Jackson & Bergeman, 2014;Nichols & Hunt, 2011;Reed & Neville, 2014), few, if any, religiously unaffiliated people are included in such studies. In a study of church and secular group members, Galen and Kloet (2011) found high certainty in participants' belief or nonbelief in god(s) was associated with higher emotional stability and life satisfaction as compared to participants' with less certainty in their (non)belief, even when controlling for demographic (e.g., age, gender) and social (social support) variables.…”
Section: Religious Coping and Natural Disastersmentioning
confidence: 99%
“…One common misunderstanding given the established link between religiosity and health is that nonreligion is "a health liability" [54, p. 370 positive/negative affect, and subjective happiness. This relationship is cross-culturally robust and has been identified in several national, ethnic, and religious contexts, ranging from the United States [29], East Germany [60], Turkey [61], and Israel [62], for example.…”
Section: Nonbelief and Health: Does Nonbelief Harm Psychological Wellmentioning
confidence: 95%
“…For example, a convinced atheist probably has difficulty answering questions on the importance of God or religion in his or her life or on the certainty of his or her religious beliefs if he or she wants to indicate that it is a central aspect in his or her life not to believe in God or adhere to a religion and that he or she is certain of his or her nonbelief. Cragun, Hammer, and Nielsen (2015) call such questions that assume religiosity as the norm and are therefore difficult to answer out of a nonreligious perspective “one‐and‐a‐half barreled items.” This might be one reason why Ellison (1991) did not find any nonlinear effects in his study because a question on the certainty of religious belief is difficult to answer for nonreligious individuals. Nonreligious individuals are not differentiated from weakly religious individuals and are often functioning as a residual group (Farias and Coleman In press; Galen 2015; Hwang, Hammer, and Cragun 2011; Moore and Leach 2016; Pasquale 2012; Zuckerman, Galen, and Pasquale 2016). Additionally, there is no differentiation between types of nonreligious individuals (e.g., atheists, agnostics, indifferent individuals, etc.…”
Section: The Positive Relationship Between Religiosity and Life Satisfactionmentioning
confidence: 99%